A mathematical model for tailoring antimicrobial packaging material containing encapsulated volatile compounds. (August 2017) - Kurek, Mia; Laridon, Yannick; Torrieri, Elena; Guillard, Valérie; Pant, Astrid; Stramm, Cornelia; Gontard, Nathalie; Guillaume, Carole
Abstract: A mathematical model describing the water content-dependent release of an antimicrobial agent (allyl isothiocyanate (AITC)) from a bio-based film to the packaging headspace was implemented. The system was characterised experimentally by assessing release kinetics and diffusivities. The model was validated by comparing simulations to experimental data. In spite of the high complexity of the system coupling moisture and antimicrobial diffusion within the packaging material and then release into headspace, the presented model provides a good enough reproduction of experimental conditions. A sensitivity study conducted on the model showed that the release kinetics of the antimicrobial agent were the most influential parameters, and that the diffusivity of moisture and AITC within the film have negligible impact. The model was then used to demonstrate the efficiency of such packaging for shelf-life optimization as it successfully inhibited the growth of bacteria. This work provides a framework that can be used for decision support systems. Industrial relevance: This work is relevant to industrial considerations as it provides a framework for decision support systems to help manufacturers and researchers to tailor their active packaging. Indeed, the development of anti-microbial applications for food packaging is a time-consuming task, that, if undertaken from a sole experimental point of view, can also be expensive. The use of the simulation framework proposed (that was experimentally validated) helps investigate and compare multiple packaging configurations. Numerical simulation are made by changing the kinetics of release parameters and initial anti-microbial content within the packaging without requiring further experiments, the main issue lying on having plausible values for the parameters. Highlights: A diffusion-reaction model to describe AITC release from inclusion complexes is proposed. The inputs were characterised experimentally and the model is experimentally validated. A sensitivity study showed the release kinetics were the most influential parameters. The sensitivity study allowed to rule out the diffusivities. The model was applied to practical cases with food containing E. coli, S. aureus and S. enteridis .